Accessory Gene Regulator (agr) Allelic Variants in Cognate Staphylococcus aureus Strain Display Similar Phenotypes - Tan, Li; Huang, Yuyang; Shang, Weilong; Yang, Yi; Peng, Huagang; Hu, Zhen; Wang, Yuting; Rao, Yifan; Hu, Qiwen; Rao, Xiancai; Hu, Xiaomei; Li, Ming; et al. (Frontiers in Microbiology, 2022)
The accessory gene regulator (agr) quorum sensing system is an important global regulatory system of Staphylococcus aureus (S. aureus) and contributes to the its pathogenicity. S. aureus agr system is divided into four agr groups based on the amino acid polymorphisms of AgrB, AgrD and AgrC. The agr activation is group-specific, resulting in variations in agr activity and pathogenicity among the four agr groups. Strains with divergent agr system always have different phenotypes. In the present report, we respectively exchanged the agr system of a certain S. aureus with other three agr alleles and assessed the corresponding phenotypes of these congenic strains. Replacement of agr system led to significant variations in hemolytic activity, protein expression and virulence gene expression comparing to that of the parental strain. Interestingly, we found that the biological characteristics of these agr congenic strains in the same strain background were highly similar to each other, and the allele-dependent differences of the agr systems were weakened. These findings indicate that the allele-dependent agr predilections of S. aureus is determined by some factors in addition to the polymorphisms of AgrB, AgrD, and AgrC. Future studies may reveal the novel mechanism to improve our understanding of the agr network.